2003
DOI: 10.1191/1352458503ms904oa
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue associated with multiple sclerosis: diagnosis, impact and management

Abstract: In patients with multiple sclerosis (MS) fatigue is the most common symptom and one of the most disabling features. As many as 40% have described it as the single most disabling symptom--a higher percentage than weakness, spasticity, motor problems, or bowel or bladder problems. The etiology and pathophysiology of MS-related fatigue remain unknown. Studies have failed to demonstrate an association between MS-related fatigue and the level of disability, clinical disease subtype, or gender, although recent data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
281
2
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(305 citation statements)
references
References 44 publications
12
281
2
10
Order By: Relevance
“…18 Sutherland et al also reported that relaxation education resulted in a decrease in fatigue levels in MS patients. 17 It is reported in the literature that carefully and regularly applied exercise is one of the methods used in coping with fatigue 8,30 ; PMRT used as one of the nonpharmacological approaches to control fatigue in patients with MS yielded positive results, 7,31 and 5-20-minute PMRT sessions were as effective as 1 hour of sleep in preserving individuals' physical energy. 32 A statistically significant difference was found between the global sleep quality ( p < 0.001) score averages and the score averages the patients obtained from subjective sleep quality ( p < 0.001), sleep latency ( p < 0.001), sleep duration ( p < 0.05), sleep efficiency ( p < 0.05), sleep disorder ( p < 0.001), and daytime dysfunction ( p < 0.001) areas of sleep quality scale after PMRT.…”
Section: Discussionmentioning
confidence: 99%
“…18 Sutherland et al also reported that relaxation education resulted in a decrease in fatigue levels in MS patients. 17 It is reported in the literature that carefully and regularly applied exercise is one of the methods used in coping with fatigue 8,30 ; PMRT used as one of the nonpharmacological approaches to control fatigue in patients with MS yielded positive results, 7,31 and 5-20-minute PMRT sessions were as effective as 1 hour of sleep in preserving individuals' physical energy. 32 A statistically significant difference was found between the global sleep quality ( p < 0.001) score averages and the score averages the patients obtained from subjective sleep quality ( p < 0.001), sleep latency ( p < 0.001), sleep duration ( p < 0.05), sleep efficiency ( p < 0.05), sleep disorder ( p < 0.001), and daytime dysfunction ( p < 0.001) areas of sleep quality scale after PMRT.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Fatigue is the most common and one of the most disabling symptoms of multiple sclerosis, experienced by around 80% of adults with the disease. [8][9][10] Multiple sclerosis-related fatigue refers to a severe and overwhelming feeling of exhaustion and lack of energy, which may result in functional impairment.11 A growing body of evidence suggests that fatigue is also a significant problem in paediatric populations, affecting approximately 30% of the general adolescent population and a substantial proportion of children and adolescents with chronic illnesses such as cancer, rheumatoid arthritis, chronic pain, and neurological conditions. [12][13][14][15][16][17] Recent evidence of fatigue in children and adolescents with multiple sclerosis (caMS) reflects these findings, with over half reporting at least mild fatigue and approximately 40% reporting fatigue severe enough to impact on school performance and recreational activities.…”
mentioning
confidence: 99%
“…Fatigue, another common symptom reported by people with MS [9], may also contribute to reduced walking capacity [10]. Muscle fatigue is known to worsen with physical activity [11] and is related to perceived fatigue levels in people with MS [12] .…”
mentioning
confidence: 99%